2010
DOI: 10.3960/jslrt.50.129
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G4 (IgG4)-Positive or -Negative Ocular Adnexal Benign Lymphoid Lesions in Relation to Systemic Involvement

Abstract: The purpose of this study is to determine the relationship of ocular adnexal benign or reactive lymphoid hyperplasia, including orbital pseudotumor, with immunoglobulin G4 (IgG4)-related diseases. Medical charts of 9 consecutive patients with ocular adnexal benign lymphoid lesions, seen in the Department of Ophthalmology, Okayama University Hospital, were reviewed, and pathological sections were restained immunohistochemically for IgG4-, IgG-, and CD138-positive plasma cells. The diagnosis of IgG4-positive les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Tissue sections were processed by standardized heating pretreatment (heating at 100°C for 30 min) for antigen retrieval prior to entering the immunohistochemical procedures. 10 In brief, the sections were incubated with 3% hydrogen peroxide for 5 min to inactivate endogenous peroxidase and blocked with 10% normal goat serum for 10 min. The sections were then incubated with primary antibodies overnight at 4°C, washed with 0.05% Tween 20-containing phosphate buffered saline three times, incubated with the secondary antibody at room temperature for 30-60 min, and washed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tissue sections were processed by standardized heating pretreatment (heating at 100°C for 30 min) for antigen retrieval prior to entering the immunohistochemical procedures. 10 In brief, the sections were incubated with 3% hydrogen peroxide for 5 min to inactivate endogenous peroxidase and blocked with 10% normal goat serum for 10 min. The sections were then incubated with primary antibodies overnight at 4°C, washed with 0.05% Tween 20-containing phosphate buffered saline three times, incubated with the secondary antibody at room temperature for 30-60 min, and washed.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10] Leukemic infiltration of the conjunctiva is rare but does occur to present the same clinical picture as lymphoma. [11][12][13][14][15] In the older literature, three patients have been described in separate case reports to develop multiple skin lesions and a conjunctival lesion in the course of acute myelomonocytic leukemia.…”
Section: Fig 4 Whole-body 2-[mentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27][28] IgG4-associated disease is now recognised as a systemic disease process. 22 Table 2 describes conditions once viewed as unique but which are now recognised by the IgG4-related systemic disease spectrum.…”
Section: Immunoglobulin G4 and Systemic Diseasementioning
confidence: 99%
“…[1][2][3][4] Retrospective IgG4 staining of orbital biopsies has revealed that IgG4-RD may account for 36% of cases originally diagnosed as idiopathic orbital inflammation, 5 and an even higher proportion of orbital lymphoid hyperplasia. 6,7 Corticosteroids are considered first-line treatment for IgG4-ROD and the response is typically excellent but unsustained. A metaanalysis of published cases of IgG4-related orbital disease (IgG4-ROD) revealed that 50% of all cases treated with corticosteroids experienced disease relapse during dose taper or shortly after corticosteroid cessation.…”
Section: Introductionmentioning
confidence: 99%